Evaluation of business strategic decisions under changing environment conditions - Zinkevičiūtė, Virgilija (Journal of Business Economics and Management, 2007)
A problem of strategic decisions evaluation under changing environment conditions is analyzed in this article. In the context of these conditions the use of scenarios’ method, integrating scenarios formation into strategic decisions evaluation process, is perspective. The combination of multicriteria evaluation and scenarios’ method allows versatile evaluation of strategic decisions in aspects of usefulness and viability regarding perspective environment situations. A universal scenarios formation technology oriented towards facilitation of scenarios creation using a graphic tool ‐ “Scenarios Roads’ Analysis” is offered. Methodological guidelines of strategic decisions evaluation applying multicriteria evaluation and scenarios’ method combination is provided as well as their acceptability tested on experiment results.First Published Online: 14 Oct 2010